Improvement of Healthy Life Behavior in Rural Families - Nino Yayah Saad; . Adiyyah; Emmy Karsin; Lilik Noor Yuliati (Media Gizi dan Keluarga, 2000)
The general objective of the research was to study healthy life behavior of rural families and to determine its influential factors. Meanwhile the specific objectives were (1) to identify healthy life behavior of rural families, (2) to determine factors affecting the behavior, and (3) to formulate effort to improve the family healthy life behavior. The research was conducted in the sub-districts of Leuwiliang and Cibungbulang, Bogor, from February to December 1999. The population of the study was families at which the father and the mother present. It was 305 families involved in the study which consisted of 194 families from Leuwiliang Sub-district and 111 families from Cibungbulang Sub-district. Collected data consist of primary and secondary data. The researchers analyzed data descriptively and employed statistical method of multiple regression analysis. The study indicates that most respondents are categorized to have good knowledge (62,1%) and good attitude (97,4%) toward nutrition and health. Meanwhile, in term of practices of healthy life, 92,8 percent of respondents are classified as having moderate category. The score of knowledge tends to be influenced by the number of obtained information, wife educational attainment, and score of attitude and practice toward health and nutrition. The attitude toward nutrition and health is affected by the level of knowledge, and the practice of healthy life is influenced by the educational attainment and the knowledge toward health and nutrition. Based on the findings, the study suggests to develop extension programs about self-cleanliness, the required need of food and nutrition, particularly for pregnant mothers, home sanitation, and proper age of supplementary feeding. The programs are basically to increase the knowledge and awareness of the parents about healthy life behavior. In addition to that, it is necessary to conduct assistance programs in tile (cement) flooring, family toilet making, air ventilation renovating, and healthy-clean water supplying.Keywords: healthy life behavior, nutrition knowledge an attitude